2019
DOI: 10.3390/molecules24193472
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Gel State Properties of Supramolecular Gels by Functional Group Modification

Abstract: The factors affecting the self-assembly process in low molecular weight gelators (LMWGs) were investigated by tuning the gelation properties of a well-known gelator N-(4-pyridyl)isonicotinamide (4PINA). The N―H∙∙∙N interactions responsible for gel formation in 4PINA were disrupted by altering the functional groups of 4PINA, which was achieved by modifying pyridyl moieties of the gelator to pyridyl N-oxides. We synthesized two mono-N-oxides (INO and PNO) and a di-N-oxide (diNO) and the gelation studies revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…We have been successful in identifying the role of various nonbonding interactions in gel formation by comparing the molecular assembly in crystalline and gel/dried gel states [ 30 , 43 , 44 , 45 ]. Although, the xerogel does not represent the exact structure of the gel state since the drying process can lead to a morphological change or phase transition [ 46 ], this approach is still recognized as the most useful strategy to unravel the self-assembly of a gelator [ 3 , 7 , 29 , 30 , 43 , 44 , 45 ]. The self-assembly of L 1 and L 2 in the gel state was correlated with respective crystal structures by comparing the powder X-ray pattern of the bulk crystals and dried gels with the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have been successful in identifying the role of various nonbonding interactions in gel formation by comparing the molecular assembly in crystalline and gel/dried gel states [ 30 , 43 , 44 , 45 ]. Although, the xerogel does not represent the exact structure of the gel state since the drying process can lead to a morphological change or phase transition [ 46 ], this approach is still recognized as the most useful strategy to unravel the self-assembly of a gelator [ 3 , 7 , 29 , 30 , 43 , 44 , 45 ]. The self-assembly of L 1 and L 2 in the gel state was correlated with respective crystal structures by comparing the powder X-ray pattern of the bulk crystals and dried gels with the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…The gel to solution transition temperature ( T gel ) was evaluated in different solvent systems using ball-drop method [ 7 , 30 , 44 , 45 ]. The required amount of the gelator was dissolved in the solvent or solvent mixtures by heating the mixture in a sealed vial to obtain a clear solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[306][307][308] Generally, the binding sites are connected to some associating units on the gelator structure that assist self-assembly involving non-covalent interactions. 18,[309][310][311] Such associating units may contain hydrophobic moieties like cholesterol 169,[312][313][314] and aromatic surface, 315 or hydrophilic functionalities like peptide, 316 sugar 317 etc. Chemical analyte responsive gels have huge potential as molecular sensors, aggregation probes, antibacterial agents, conducting materials and water purifying agents.…”
Section: (Vii) Post Assembly Fabrication Of Gels By Chemical Analytesmentioning
confidence: 99%
“…The modification of these functional groups will lead to the alteration of specific interactions arising from the particular functional group, which can be considered as an excellent strategy to evaluate the role of specific interactions in gel formation [30,31]. For example, Zinchuan et al have synthesized a cholesterol-based dendrimer gelator from the parent terminal alkyne-based gelator and have shown that the modified compounds formed gel in polar solvents compared to the parent compound, which only formed gel in nonpolar solvents [32].…”
Section: Introductionmentioning
confidence: 99%